Reinvigorating Urban Under Space: Towards a New Type of Public Landscape - Wang, Yujia; Cai, Gandong (Nakhara : Journal of Environmental Design and Planning, 2017)
The proposition of this paper is to examine the agency of landscape in subverting, energizing and reinvigorating a specific kind of deserted space in cities - Urban Under Space. The term Urban Under Space refers to residual infrastructural spaces, such as under-bridge space, abandoned subway stations, air raid shelters, etc. The wide availability and continued generation of Urban Under Space in cities that were investigated in North America and Asia reflect a problem in modern planning. But it also provides an opportunity of positioning these pieces as a network of new urban landscapes that can offer a unique and attractive public space experience. The paper provides an elaboration of the invented term, a case analysis of the creative re-use of Air Raid Shelters in Chongqing, and a systematic research to prototype the issues and opportunities as related to such spaces. The paper also discusses its potential as a ground for unique urban public experiences.